Association Between Cardiovascular Risk Factors and the Severity of Coronavirus Disease 2019: Nationwide Epidemiological Study in Korea - Kong, Kyoung Ae; Jung, Sodam; Yu, Mina; Park, Junbeom; Kang, In Sook (Frontiers in Cardiovascular Medicine, 2021)
Background: Acute respiratory viral infections can result in cardiovascular involvement, with such patients having a significantly higher mortality rate than those without cardiovascular involvement. Due to the ongoing coronavirus disease 2019 (COVID-19) pandemic, it is important to determine whether cardiovascular risk factors are associated with the severity of COVID-19. Methods: These nationwide data were provided by the Korea Disease Control and Prevention Agency. We defined a patient as having a “critical illness” if they required more than invasive mechanical ventilation and “fatal illness” if they died. Results: Among the total 5,307 patients, 2,136 (40.8%) were male. The critical illness rate was 5.1% (males: 6.7, females: 4.0%) and the fatality rate was 4.54%. The multivariable analysis showed that age ≥60 years, male sex, diabetes mellitus, hypertension, heart failure, chronic kidney disease, cancer, and dementia were independent risk factors for critical illness. The risk scoring model showed the significance of multiple risk factors. Patients with four risk factors; old age (≥60 years), male sex, hypertension, and diabetes mellitus had a more than a 100 times higher risk for severe COVID-19 than those without these risk factors (OR; 95% confidence interval, 104; 45.6–240.6 for critical, 136.2; 52.3–3547.9 for fatal illness). Conclusions: This study demonstrated that cardiovascular risk factors are also significant risk factors for severe COVID-19. In particular, patients who have multiple cardiovascular risk factors are more likely to progress to severe COVID-19. Therefore, early and appropriate treatment of these patients is crucial.